2013
DOI: 10.1136/thoraxjnl-2012-202348
|View full text |Cite
|
Sign up to set email alerts
|

Using socio-demographic and early clinical features in general practice to identify people with lung cancer earlier

Abstract: IntroductionIn the UK, most people with lung cancer are diagnosed at a late stage when curative treatment is not possible. To aid earlier detection, the sociodemographic and early clinical features predictive of lung cancer need to be identified. Methods We studied 12 074 cases of lung cancer and 120 731 controls in a large general practice database. Logistic regression analyses were used to identify the socio-demographic and clinical features associated with cancer up to 2 years before diagnosis. A risk predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 26 publications
7
85
0
1
Order By: Relevance
“…A history or diagnosis of emphysema should be an interesting additional criterion for better defining at-risk populations [31][32][33]. Although many authors have reported their risk scores, most were validated retrospectively [34,35]. An exception is the UKLS trial's LLP score, which was tested in a prospective trial [13,36].…”
Section: What Is New In Screening Optimization?mentioning
confidence: 97%
“…A history or diagnosis of emphysema should be an interesting additional criterion for better defining at-risk populations [31][32][33]. Although many authors have reported their risk scores, most were validated retrospectively [34,35]. An exception is the UKLS trial's LLP score, which was tested in a prospective trial [13,36].…”
Section: What Is New In Screening Optimization?mentioning
confidence: 97%
“…These models show AUC values of 0.88-0.92 for predicting lung cancer [23,24]. One model was developed from data recorded between 4 and 12 months prior to the diagnosis of lung cancer, thus reflecting factors that might help to bring the diagnosis forward [23]. Employing this model would reduce the number of chest X-rays required to diagnose one lung cancer from 421 using conventional referral criteria to 119.…”
Section: Identification Of Early Symptomatic Diseasementioning
confidence: 99%
“…In the UK this has been possible by using large primary care datasets of routinely collected data. These models show AUC values of 0.88-0.92 for predicting lung cancer [23,24]. One model was developed from data recorded between 4 and 12 months prior to the diagnosis of lung cancer, thus reflecting factors that might help to bring the diagnosis forward [23].…”
Section: Identification Of Early Symptomatic Diseasementioning
confidence: 99%
“…Therefore, the use of an accurate model that incorporates additional risk factors to select persons for screening is likely to be cost-effective and will reduce harm to people with the least risk of lung cancer [33,51]. Individualized risk estimation has been developed in several models [52,53,54]. The PLCO cancer screening trial lung cancer risk model was developed from the largest dataset known to date.…”
Section: Discussionmentioning
confidence: 99%